Ghilarducci, Teresa. Work, Retire, Repeat: The Uncertainty of Retirement in the New Economy - Samwick, Andrew (Journal of Economic Literature, 2025)
Andrew Samwick of Dartmouth College and NBER reviews “Work, Retire, Repeat: The Uncertainty of Retirement in the New Economy” by Teresa Ghilarducci. The Econlit abstract of this book begins: “Explores the implications of compelling older people to work longer, presenting a pro-worker alternative that, instead of cutting pensions and forcing work on elders, enforces anti-age-discrimination laws, institutes effective job training, and pays for good pensions and more Social Security benefits.”